Co-expression of stress-responsive regulatory genes, MuNAC4, MuWRKY3 and MuMYB96 associated with resistant-traits improves drought adaptation in transgenic groundnut (Arachis hypogaea l.) plants - Venkatesh, Boya; Vennapusa, Amaranatha R.; Kumar, Nulu Jagadeesh; Jayamma, N.; Reddy, B. Manohara; Johnson, A. M. Anthony; Madhusudan, K. V.; Pandurangaiah, Merum; Kiranmai, K.; Sudhakar, Chinta (Frontiers in Plant Science, 2022)
Groundnut, cultivated under rain-fed conditions is prone to yield losses due to intermittent drought stress. Drought tolerance is a complex phenomenon and multiple gene expression required to maintain the cellular tolerance. Transcription factors (TFs) regulate many functional genes involved in tolerance mechanisms. In this study, three stress-responsive regulatory TFs cloned from horse gram, (Macrotyloma uniflorum (Lam) Verdc.), MuMYB96, involved in cuticular wax biosynthesis; MuWRKY3, associated with anti-oxidant defense mechanism and MuNAC4, tangled with lateral root development were simultaneously expressed to enhance drought stress resistance in groundnut (Arachis hypogaea L.). The multigene transgenic groundnut lines showed reduced ROS production, membrane damage, and increased superoxide dismutase (SOD) and ascorbate peroxidase (APX) enzyme activity, evidencing improved antioxidative defense mechanisms under drought stress. Multigene transgenic plants showed lower proline content, increased soluble sugars, epicuticular wax content and higher relative water content suggesting higher maintenance of tissue water status compared to wildype and mock plants. The scanning electron microscopy (SEM) analysis showed a substantial increase in deposition of cuticular waxes and variation in stomatal number in multigene transgenic lines compared to wild type and mock plants. The multigene transgenic plants showed increased growth of lateral roots, chlorophyll content, and stay-green nature in drought stress compared to wild type and mock plants. Expression analysis of transgenes, MuMYB96, MuWRKY3, and MuNAC4 and their downstream target genes, KCS6, KCR1, APX3, CSD1, LBD16 and DBP using qRT-PCR showed a two- to four-fold increase in transcript levels in multigene transgenic groundnut plants over wild type and mock plants under drought stress. Our study demonstrate that introducing multiple genes with simultaneous expression of genes is a viable option to improve stress tolerance and productivity under drought stress.